Retinoic Acid Receptor Agonists Suppress Muscle Fatty Infiltration in Mice. Issue 2 (February 2021) - Shirasawa, Hideyuki; Matsumura, Noboru; Yoda, Masaki; Okubo, Kazumasa; Shimoda, Masayuki; Uezumi, Akiyoshi; Matsumoto, Morio; Nakamura, Masaya; Horiuchi, Keisuke
Background: The infiltration of fat tissue into skeletal muscle, a condition referred to as muscle fatty infiltration or fatty degeneration, is regarded as an irreversible event that significantly compromises the motor function of skeletal muscle. Purpose: To investigate the effect of retinoic acid receptor (RAR) agonists in suppressing the adipogenic differentiation of fibroadipogenic progenitors (FAPs) in vitro and fatty infiltration after rotator cuff tear in mice. Study Design: Controlled laboratory study. Methods: FAPs isolated from mouse skeletal muscle were cultured in adipogenic differentiation medium in the presence or absence of an RAR agonist. At the end of cell culture, adipogenic differentiation was evaluated by gene expression analysis and oil red O staining. A mouse model of fatty infiltration—which includes the resection of the rotator cuff, removal of the humeral head, and denervation the supraspinatus muscle—was used to induce fatty infiltration in the supraspinatus muscle. The mice were orally or intramuscularly administered with an RAR agonist after the surgery. Muscle fatty infiltration was evaluated by histology and gene expression analysis. Results: RAR agonists effectively inhibited the adipogenic differentiation of FAPs in vitro. Oral and intramuscular administration of RAR agonists suppressed the development of muscle fatty infiltration in the mice after rotator cuff tear. In accordance, we found a significant decrease in the number of intramuscular fat cells and suppressed expression in adipogenic markers. RAR agonists also increased the expression of the transcripts for collagens; however, an accumulation of collagenous tissues was not histologically evident in the present model. Conclusion: Muscle fatty infiltration can be alleviated by RAR agonists through suppressing the adipogenic differentiation of FAPs. The results also suggest that RAR agonists are potential therapeutic agents for treating patients who are at risk of developing muscle fatty infiltration. The consequence of the increased expression of collagen transcripts by RAR agonists needs to be clarified. Clinical Relevance: RAR agonists can be used to prevent the development of muscle fatty infiltration after rotator cuff tear. Nevertheless, further studies are mandatory in a large animal model to examine the safety and efficacy of intramuscular injection of RAR agonists.